How Consistently Do We Measure Bruises? A Comparison of Manual and Electronic Methods. (27th February 2013) - Lawson, Zoë; Dunstan, Frank; Nuttall, Diane; Maguire, Sabine; Kemp, Alison; Young, Stephen; Barker, Michael; David, Laura; Appleton, Jane V.; Sidebotham, Peter
<x xml:space="preserve">Abstract</x> Bruises in suspected abuse are routinely measured for clinical and forensic purposes. We aimed to determine the consistency of electronic and manual bruise measurements. Over two sessions, 45 observers recorded the greatest lengths of eight bruises in cross‐polarised images. Observers were presented with six images in each session; four were common to both sessions. Manual measurements were achieved using a paper tape‐measure on hard‐copy images; electronic measurements used ImageJ software for digital on‐screen images. Differences in mean measurements between methods were tested using paired t‐tests; within‐ and between‐observer variations were computed. On average, manual measurements were smaller than electronic measurements. Observers were prone to rounding bias in manual measurements. Overall standard deviations of measurements (0.39–0.63 cm) did not differ greatly between methods. Measuring electronically, observers showed more consistency between sessions than measuring manually. Electronic measurements had greater variation between observers than manual measurements. Overall, 95 per cent of measurements for a given bruise lay within a range of 2 cm. We conclude that measurement of a bruise by either method varied. In clinical practice, we recommend that a right‐angled linear scale is included in any photographic image of a bruise, such that clinicians can standardise the estimate of bruise size. Copyright © 2013 John Wiley & Sons, Ltd. <boxed-text content-type="pullQuote" id="car2217-blk-0001" position="anchor" orientation="portrait"> '45 observers recorded the greatest lengths of eight bruises in cross‐polarised images' </boxed-text> <boxed-text content-type="pullQuote" id="car2217-blk-0002" position="anchor" orientation="portrait"> 'We recommend that a right‐angled linear scale is included in any photographic image of a bruise' </boxed-text> Key Practitioner Message: Measurements produced by different observers varied widely when assessing the same bruise Less variation was found when observers repeated the measurement electronically, than when done manually In contrast, electronic measurements varied more than manual measurements between different observers Defining the boundary of a bruise allows a more detailed assessment of size, shape, location, pattern, and colour Including a right‐angled linear scale is recommended in any photographic image of a bruise